Pengaruh Kinerja dan Kualitas Pelayanan Helpdesk Terhadap Kepuasan Karyawan Pada Universitas Prasetiya Mulya Tangerang: The Effect of Helpdesk Performance and Service Quality on Employee Satisfaction at Prasetiya Mulya University, Tangerang - Umunaela, Umunaela; Nurhadi, Nurhadi; Hadi, Seno Sudarmono (Jurnal Mnajemen | Ekonomi | Akuntansi, 2026)
this research was conducted at Prasetiya Mulya University with the objective of examining the influence of performance (X1) and Helpdesk service quality (X2) on employee satisfaction (Y). The population of this research consisted of employees at Prasetiya Mulya University, Tangerang. The sampling technique employed was non-probability sampling with a purposive sampling approach. A total of employees were selected as the research sample. Data were analyzed using a quantitative method with the assistance of IBM SPSS Statistics Version 21. The finding of this study indicate that: 1) Performance (X1) has a positive and significant effect on employee satisfaction (Y), with a coefficient value of 3,671. 2) Helpdesk service quality (X2) has a positive and significant effect on employee satisfaction (Y), with a coefficient value of 5,361. 3) Performance (X1) and Helpdesk service quality (X2) simultaneously have a significant effect on employee satisfaction (Y), with a combined value of 90,793. 4) The regression equation obtained in this study is: Y = 2,631 + 0,937 X1 + 1,312 X2. Keywords: Performance1, Helpdesk Service Quality2, Employee Satisfaction